Green Synthesis of SP-SeNPs as Promising Antioxidant Agent and Pancreatic Lipase Inhibitor - Shawky, Suzan; A. Ali, Ali; Abdalla Hussein, Mohammed (Asian Journal of Chemistry, 2022)
The purpose of this study was to evaluate pancreatic lipase inhibitory activity and antioxidant effect of Spirulina platensis containing selenium nanoemulsion nanoparticles (SP-SeNPs). The SP-SeNPs were prepared and characterized to find mean particle size and zeta potential to evaluate the possible lipoprotein lipase and pancreatic lipase inhibitory as well as antioxidant and free radical scavenging activities. Different antioxidant tests were employed, namely, reducing power, chelating activity on Fe2+, free radical-scavenging and total antioxidant activities. The obtained results showed that the shapes of SP-SeNPs were spherical and the mean particle size was 39.86 ± 0.14 nm and negative zeta potential was +33.14. The SP-SeNP at 60 ppm and epicatechin (100 ppm) produce the same ratio of inhibition 18%. However, lipoprotein lipase activity was increased to less than 20 and 27 % at 80 and 100 ppm SP-SeNPs. Also, the present results indicate that the SP-SeNPs at concentration of 80 and 100 ppm showed inhibitory effects more than epicatechin (100 ppm) against pancreatic lipase activity. However, the reducing power of SP-SeNPs and butylated hydroxytoluene (BHT), butylated hydroxy anisole (BHA) and α-tocopherol decreased in the order of BHA> SP-SeNPs >BHT > α-tocopherol. The chelating activity of samples increased with increasing incubation times with FeCl2. However, the chelating activity of SP-SeNPs of 1.50 mg/mL was nearly equal to EDTA at 0.037 mg/mL (43.67%) for an incubation time of 60 min. This indicates that the chelation property of the samples on Fe2+ ions may afford protection against oxidative damage. The SP-SeNPs of 6 mg/mL had the highest radical scavenging activity when compared with 0.6 mg/mL Trolox. The antioxidant activity of SP-SeNPs and both standards decreased in the order of SP-SeNPs > α-tocopherol > Trolox > BHA > BHT. The results suggested that the inhibitory activity of SP-SeNPs is closely related to the tertiary structural change in lipoprotein lipase and pancreatic lipase. Also, the antioxidant activity of SP-SeNPs could be due to presence of carotenoids, w-3 or w-6 polyunsaturated fatty acid, g-linolenic acid, sulpholipides, glycolipids, potassium, zinc and selenium, vitamin A, vitamin E and a variety of minerals.